Cyclical patterns in volcanic degassing revealed by SO2 flux timeseries analysis: An application to Soufriere Hills Volcano, Montserrat - Nicholson, E; Mather, T; Pyle, D; Odbert, H; Christopher, T (2013)
Cyclical patterns of behaviour in timeseries of seismic and geodetic data at volcanoes are frequently observed during lava dome-building eruptions, and are particularly well-documented from the current eruption of the Soufrière Hills Volcano (SHV), Montserrat. However, the discontinuous nature of many SO2 measurements often preclude the identification and quantitative analysis of cyclical patterns in degassing data. Here, using a long SO2 timeseries from SHV, with continuous measurements since 2002, we explore for the first time degassing behaviour at a resolution comparable to that possible for seismic and deformation datasets. Timeseries analysis of flux data spanning 2002-2011 reveals that SO2 emissions at SHV exhibit complex cyclicity, with dominant cycles evident on both multi-year and multi-week (~50 day) timescales. These cycles persist through phases of both active extrusion and eruptive pause, and show close similarities to periodic components previously identified at SHV in timeseries of seismicity, ground deformation and lava extrusion.The strength of expression or amplitude of degassing cycles, particularly on multi-week timescales, shows distinct temporal variation, and appears to correlate with the occurrence and nature of explosive activity occurring in 2002-2009. This suggests that the amplitude of surface gas flux cycles is modulated by physical conditions within the conduit. Direct quantitative comparison between seismicity, dome growth, and degassing for eruptive Phases 2 (2002-2003) and 3 (2005-2007) reveals that peaks in SO2 flux appear to correspond broadly to enhanced lava extrusion and elevated seismicity within cycles of 30-50 days. However, time lags of 2, 4 and 7 days are observed between initial low-frequency seismic swarms and peaks in dome growth, SO2 flux and rockfall event rate respectively. Multi-parameter correlations offer valuable insights into the controls on subsurface gas ascent, but further research is required to fully explore the contributions of permeability and overpressure, as well as other subsurface processes. © 2013 The Authors.